Information System Audit Using COBIT and ITIL Framework: Literature Review - Rusman, Arif; Nadlifatin, Reny; Subriadi, Apol Pribadi (Politeknik Ganesha Medan, 2022)
Improved IT performance drives business growth, enhances competitive advantage, and enables strategic improvements in IT management and governance. This condition is increasingly important because business organizations and systems and technology are increasingly complex. In the application and use of technology, information technology audits require a framework based on principles that drive the desired behavior. In writing this literature review, the information technology audit method used is ITIL, and COBIT as guidelines for corporate information technology governance and audit processes. In its use, the ITIL framework is designed to ensure a flexible, coordinated and integrated system for the effective governance and management of IT services. While the COBIT framework is designed from a number of components that function to adjust, maintain, and shape system governance. To conduct an information system audit, the authors need to pay attention to things that can affect IT performance. This study produces a model to determine the factors that affect the Information System Audit. Researchers conducted a literature review from various sources that discussed Information System Auditing Using the COBIT and ITIL Frameworks which were collected from some of the literature found. Several factors that influence the Information System Audit are Design Factors, Knowledge Worker factors, Operational factors, Risk Assessment Factors, and Gather Evidence Factors. The author also conducted a systematic mapping study to find research gaps, namely the method of mapping the relationship between research topics and how much research has covered each topic and the relationship between topics.